The impact of co-working office’s facilities toward work environment in Kuala Lumpur / Muhammad Afiq Najmuddin Malek - Malek, Muhammad Afiq Najmuddin (2021)
Co-working is an arrangement in which many employees from separate organizations share an office room, cost savings, and flexibility through the use of shared facilities, such as equipment, facilities, and receptionist, and custodial services. The facilities are one of the important parts of co-working where with good facilities it will create a good work environment. There are several types of facilities which are, networking, community building, vibrant meeting, and training rooms. The lack of good facilities will affect the work environment and with that problem, it can lead to unsuccessful co-working office. This research aim is to study identify the impact of co-working facilities on the work environment that can enhance the daily work productivity among the users. This research is predicated on data obtained from a survey questionnaire. The data were analyzed to evaluate and determine the work environment in coworking space that influences the productivity of the users. Therefore, this study also gives the data about various information regarding the specific of co-working facilities. Such as, the advantage of co-working facilities toward the users and the services that are been provided for each facility. The research suggested that the coworking space should consider improving its space regarding the user demand to enhance the quality of the work environment because it is an important key to user success. It is hoped that the study can contribute to the improvement of the current coworking space in Kuala Lumpur.